A historicidade dos textos no ensino de gêneros orais à luz das tradições discursivas e do interacionismo sociodiscursivo - Rodrigues, Ticiane (2023)
This research investigates the teachable dimensions of the controlled genre debate that allows us to think of the historicity of texts, especially the oral text, through a teaching itinerary. Our work is based on the Discursive Traditions (TD) proposed by Koch (1997), Kabatek (2001, 2006), Gomes (2007), Zavam (2009), Longhin (2014) and Castilho, Andrade and Gomes (2018), once, when pointed out the historicity of texts, it is necessary to pin down the factors and actions that influence the constitution of the linguistic-discursive features of these very texts. Regarding the Sociodiscursive Interactionism (SDI) approach, we are in line with the works of Bronckart (1999), Schneuwly and Dolz (2011), By Pietro e Schneuwly (2006). The adopted conception of Didactic Itinerary derives from the studies of Colognesi and Dolz (2017). This reference framework provided the necessary elements to defend that texts and discourses are constructed in enunciative activities, and, as a result, intersubjective, interactional and socio-cognitive practices emerge. For that reason, we do not take “text” and “discourse” for fully fledged products, but for contextually situated units of meaning that allows different construction processes over time. To help us detail the global and central aspects of speaking, which are meant to be evaluated by means of the activities proposed in the teaching itinerary, we have adopted some contributions from Conversation Analysis (CA), such as Marcuschi (2001) and Fávero, Andrade and Aquino (2007). Furthermore, we based the understanding of the spoken text structuring on Jubran (2006) and Jubran and Koch (2006). To support the creation of school activities, we anchored our research in Didactic Engineering, mainly discussed by Dolz (2016) and which emerges as an essential tool to the comprehension of the pragmatic sense of planning school activities while an achievable and likely objective is pursued. This dissertation is a qualitative one, as it emphasizes oral genres teaching by means of integrative activities in a didactic itinerary system. In turn, this very system encompasses the historicity of oral genres. Methodologically, we designed a theoretical-methodological and analytical path which helped us systematize native language teaching using an oral genre. The proposed itinerary, along with the planned activities, allowed a more precise outline of the regulated debate – taken as a discursive genre – in such a manner that the proposed activities contributed to the construction of the historicity of this oral genre, based on examples of past synchronies. These activities have proved necessary when it came down to teaching global and local oral aspects, which are constitutive of the oral genre. We hope that the theoretical-methodological path undertaken together, along with the proposal of a didactic itinerary which conceives the teaching of orality and the historicity of texts, may also prove itself to be useful for future research. To that effect, our hopes are that the theoretical, methodological and pedagogical implications prove themselves relevant to the area of studies on genres in general, especially when it comes to oral genres.